Formation of high δ18O fayalite-bearing A-type granite by high temperature melting of granulitic metasedimentary rocks, southern China - Huang, H.; Li, X.; Li, W.; Li, Zheng-Xiang (Geological Society of America, 2011)
The genesis of A-type granites has been controversial. Fayalite granite is a member of the most reduced A-type granites, commonly thought to have been primarily sourced from tholeiitic rocks. In this paper we report petrography, whole-rock geochemistry, Sr-Nd isotope, and in situ zircon Hf-O isotope results for a fayalite-bearing A-type granite suite at Jiuyishan in southern China. High zircon δ18O (8.0‰–9.8‰), negative zircon εHf(t) (–6.2 to –2.3), and evolved whole-rock Sr-Nd isotopes (ISr = 0.7151–0.7181; εNd(t) = –7.4 to –6.6) indicate the reworking of old supracrustal rocks. Isotopic and geochemical results, particularly downward inflections of Zr and Ba at ~70 wt% SiO2, point to fractional crystallization rather than magma mixing as the controlling process for the evolution of the igneous suite. Integrated petrological, geochemical, and isotopic studies present the first convincing case that reduced A-type granites can also be generated by high-temperature (>960 °C) melting of granulitic metasedimentary rocks, likely related to the upwelling of the asthenosphere and/or underplating and intrusion of basaltic melts. We emphasize that key factors for the genesis of this unique rock type are low oxygen fugacity (fO2 ), low fH2O, and high temperature.